2019
DOI: 10.3390/molecules24040657
|View full text |Cite
|
Sign up to set email alerts
|

Active Components, Antioxidant, Inhibition on Metabolic Syndrome Related Enzymes, and Monthly Variations in Mature Leaf Hawk Tea

Abstract: Hawk tea is a rich and edible resource, traditionally used as a beverage in South China. This drink has many pharmacologic effects, such as acting as an antioxidant and reducing blood sugar and lipids. The objective of this work was to explore the active compound contents, bioactivities and their monthly changes, and optimize the harvest time. In the present study, Hawk tea from each month in 2017 was collected and extracted with 70% (v/v) ethanol. The contents of the total flavonoids and total phenols were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The reducing power was determined using the method described previously ( 13 ). The positive control was BHT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reducing power was determined using the method described previously ( 13 ). The positive control was BHT.…”
Section: Methodsmentioning
confidence: 99%
“…The DPPH radical-scavenging activities of LBMP-2 were determined using the method described previously ( 13 ). BHT was used as the positive control.…”
Section: Methodsmentioning
confidence: 99%
“…The lignans and phenolic compounds were assayed for inhibition of pancreatic lipase by a previously described method [51] with minor modifications. In this colorimetric assay, a lipase solution (0.21 mg/mL prepared in 0.1 M phosphate buffer (pH 7.0)) was pre‐incubated with various compound solutions (0–500 μM in DMSO) on ice.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of studies have shown that polyphenols and flavonoids have strong antioxidant properties (Chen et al, 2020;Ji et al, 2020). It was found that the polysaccharide and flavonoid of hawk tea had good antioxidant activity (Chen et al, 2019;Tan et al, 2016;Xiao, et al 2017). However, it is unclear which kind of substance has a significant correlation with the antioxidant activity of hawk tea.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…As a traditional heat‐relieving beverage in the hot and humid areas of Chishui River Basin, China, hawk tea can relieve heat and thirst and alleviate distention (Xi et al., 2015). It also has antidiabetic (Lu et al., 2010), hypolipidemic (Zhao, 2013), antioxidant (Chen et al., 2019), antimicrobial (Yu et al, 2016), and hepatoprotective activity (Jia and Yuan, 2019) as well as anti‐inflammatory properties (Liu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%